Implementation of the TOPSIS Method for a Decision Support System in Recommending Tourist Destinations in Tabanan - Anggara Putra, I Wayan Kintara; Agastyar Priatdana, Gde Yoga (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
Tourism development plays an important role in stimulating regional economic growth, particularly in areas with diverse natural and cultural attractions such as Tabanan Regency in Bali. However, visitors often experience difficulties in selecting destinations that match their preferences due to the presence of multiple decision factors and scattered informational resources, making destination decisions less systematic and potentially inconsistent. This situation highlights the need for a methodical decision support mechanism capable of evaluating tourist destinations based on multiple criteria. Motivated by this issue, this study implements the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method as part of a Decision Support System designed to recommend suitable tourist destinations in Tabanan. The system evaluates nine destinations based on eight criteria, which include accessibility, attractiveness, facility availability, cleanliness, cost, popularity, safety, and visitor density, and applies weight values determined through expert judgment. The evaluation results show that Jatiluwih Rice Terrace has the highest ranking with a closeness coefficient of 0.679126, followed by Ulun Danu Beratan and Tanah Lot, indicating that heritage value and environmental management strongly contribute to recommendation outcomes. The model provides transparent ranking reasoning and can support tourists, planners, and local tourism administrators in making informed decisions. Future development may involve expanding the destination dataset, integrating real-time visitor data, and deploying the system as a mobile application to improve personalization and accessibility.